Ekphrasis - Chameleon of Literary studies “Theory and History of Ekphrasis: Results and Prospects of Study” Siedlce, 2018 - Troitsky, Nóra (Slavica, 2020)
This article aims to highlight the various methods in which ekphrasis can be analysed and new interpretations of the phenomenon in the monograph “The Theory and History of Ekphrasis: Results and Prospects of the Study” published for the 15th year anniversary of the previous work “Ekphrasis in Russian Literature” (2002). The articles touch upon the history of the study of ekphrasis, its typology, the dynamics of its functions as well as the poetics of description in the history of literature, theory and classification, including the theme of narratology, and works containing analysis from autobiographical points of view. The novelty of the monograph is that it also includes contemporary fiction which provides an excellent opportunity to redefine and reinterpret the phenomenon.